Legal Problems Regarding State Financial Losses Due to Corruption in State-Owned Enterprises (Research Study at the Bogor Regency District Attorney's Office) - Chaniago, Rizky; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. The element of corruption in BUMN Persero is state losses. Based on the definition of state finances contained in Article 2 letter g of Law No. 17 of 2003 concerning State Finances. However, this provision differs in the substance of the BUMN Law which states that BUMN Persero is a private legal entity that has its own independence. There is an overlap of several rules which on the one hand state that the money has been transferred to the BUMN's own finances and on the one hand state that the money is absolutely state finances. The aim of this research is to find out and analyze (1) the existence of BUMN in the Indonesian state administration system from a state financial perspective, (2) the pattern of law enforcement for criminal acts of corruption in BUMN which cause losses to state finances, (3) the solution concept in overcoming legal problems regarding the element of state losses due to criminal acts of corruption in BUMN. The aproach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Based on the of the research and discussion, it can be concluded: (1) In relation to the management of state finances separated in BUMN, the Law on State Finances confirms that state assets separated in BUMN are legally normatively included in state finances as regulated in Article 2 letter g which states that state assets/regional assets managed independently or by other parties in the form of money, securities, receivables, goods, and other rights that can be valued in money, including assets separated in state companies/regional companies; (2) If legally normatively in describing the pattern of law enforcement against corruption in BUMN without considering the problematic ambiguity of the latest BUMN Law with the Corruption Law, the patterns revealed by the Prosecutor in law enforcement against corruption in BUMN include proof in calculating state financial losses; (3) There is a major indication of the creation of hidden resistance for BUMN officials if legal provisions are not accompanied by strict accountability tools. This concern is justified considering that not all business policy-making is within the framework of public interest; There are times when a wrong business decision can be disguised as a strategic policy when in fact there is a conflict of interest involved.